Real-time surveillance of surgical margins via ICG-based near-infrared fluorescence imaging in patients with OSCC - Jiongru Pan; Han Deng; Shiqi Hu; Chengwan Xia; Yongfeng Chen; Jianquan Wang; Yuxin Wang (World Journal of Surgical Oncology, 2020)
Abstract Background Local recurrence is the main cause of death among patients with oral squamous cell carcinoma (OSCC). This study assessed near-infrared fluorescence (NIF) imaging and spectroscopy to monitor surgical margins intraoperatively for OSCC. Methods Cytological and animal experiments were first performed to confirm the feasibility of monitoring surgical margins with NIF imaging and spectroscopy. Then, 20 patients with OSCC were included in the clinical trials. At 6–8 h after 0.75 mg/kg indocyanine green (ICG) injection, all patients underwent surgery with NIF imaging. During the surgery, both NIF images and quantified fluorescence intensity were acquired to monitor the surgical margins. Results In cytological and animal experiments, the results showed it was feasible to monitor surgical margins with NIF imaging and spectroscopy. Fluorescence was detected in primary tumors in all patients. The fluorescence intensities of the tumor, peritumoral, and normal tissues were 398.863 ± 151.47, 278.52 ± 84.89, and 274.5 ± 100.93 arbitrary units (AUs), respectively (P < 0.05). The SBR of tumor to peritumoral tissue and normal tissues was computed to be 1.45 ± 0.36 and 1.56 ± 0.41, respectively. After primary tumor excision, the wounds showed abnormal fluorescence in four patients (4/20), and residual cancer cells were confirmed by pathological examination in two patients (2/20). Conclusion These findings confirmed the complementary value of NIF imaging during radical tumor resection of OSCC. Before tumor resection, we could utilize the fluorescence margin produced by ICG NIF imaging to determine the surgical margin. Moreover, after tumor blocks were removed, the status of surgical margin could also be evaluated rapidly by ICG NIF imaging of tumor bed and in vitro specimens.